2007
DOI: 10.1016/j.cell.2007.05.055
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis for Activation of the Receptor Tyrosine Kinase KIT by Stem Cell Factor

Abstract: Stem Cell Factor (SCF) initiates its multiple cellular responses by binding to the ectodomain of KIT, resulting in tyrosine kinase activation. We describe the crystal structure of the entire ectodomain of KIT before and after SCF stimulation. The structures show that KIT dimerization is driven by SCF binding whose sole role is to bring two KIT molecules together. Receptor dimerization is followed by conformational changes that enable lateral interactions between membrane proximal Ig-like domains D4 and D5 of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
370
3
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 304 publications
(392 citation statements)
references
References 36 publications
17
370
3
2
Order By: Relevance
“…3D). The structure of D7 dimer is very similar to the homotypic D4 contacts seen in KIT extracellular dimer structure (PDB code: 2E9W) (8). In addition D7 of VEGFR2 exhibits strong polarization of electrostatic field with an overall negatively charged surface with the exception of a positively charged center strip right along the D7-D7 interface (Fig.…”
Section: Resultsmentioning
confidence: 61%
See 3 more Smart Citations
“…3D). The structure of D7 dimer is very similar to the homotypic D4 contacts seen in KIT extracellular dimer structure (PDB code: 2E9W) (8). In addition D7 of VEGFR2 exhibits strong polarization of electrostatic field with an overall negatively charged surface with the exception of a positively charged center strip right along the D7-D7 interface (Fig.…”
Section: Resultsmentioning
confidence: 61%
“…An evolutionarily conserved sequence motif (L∕IxRΦxxxD∕ExG) responsible for mediating homotypic contacts between Ig-like domains was identified by structure-based sequence alignment of D4 of KIT, PDGFRα, PDGFRβ, and colony stimulating factor 1 receptor (CSF1R) (8,10). To determine which domain of VEGFR2 may be functionally related to D4 of KIT, we searched the sequences of D4 and D7 of VEGFRs for this conserved motif.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2B) Elegheert et al 2011;Ma et al 2012;Felix et al 2013). D4 shares a dimerization domain sequence fingerprint that has been identified in other closely related RTK III receptors, Kit and PDGFR (Yuzawa et al 2007;Yang et al 2008), and the presence of domains D4 and D5 in the CSF-1:CSF-1R D1 -D5 significantly decreases the K d of interaction Elegheert et al 2011;Ma et al 2012) owing to CSF-1R homotypic interactions. However, the K d for the CSF-1:CSF-1R D1 -D5 interaction at 37˚C ( 20 nM, human and mouse [Elegheert et al 2011]) was still higher than the dissociation constants reported for the binding of mouse (0.4 nM ]) or human (0.1 nM ) CSF-1 to their cognate receptors on cells, suggesting a significant contribution of the transmembrane domain and spatial confinement of the membrane to affinity (Fig.…”
Section: Csf-1/csf-1r and Il-34/csf-1r Complex Structuresmentioning
confidence: 99%